Pengaruh Budaya Organisasi, Lingkungan Kerja Fisik dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Biro Organisasi Sistem Pemerintahan Sekretariat Daerah Provinsi Kalimantan Selatan - Amima, Sharfina Puteri; Taharuddin, Taharuddin (JURNAL BISNIS DAN PEMBANGUNAN, 2023)
This purpose of this research is to test the effect of Organizational Culture, Physical Work Environment and Work Discipline on Employee Performance. This study uses a quantitative approach with the type of explanatory research. The sampling technique of non-probability sampling was used on 44 employees who were actively working in the Bureau of Organizational Assistants of the Regional Secretariat of the Government of South Kalimantan Province. The data obtained from the distribution of questionnaires were analyzed using a quantitative/statistical approach. The results showed that organizational culture, physical work environment and employee discipline had a positive and significant effect on employee performance. Keywords:  Organizational Culture, Physical Work Environment, Work  Discipline, Employee Performance.